Total Synthesis and Antimicrobial Evaluation of Pagoamide A - Wu, Cheng-Han; Chu, John (Frontiers in Chemistry, 2021)
Natural products are often the starting point for drug development and also the testing ground for synthetic methods. Herein we describe the total synthesis and antimicrobial evaluation of a marine natural product, pagoamide A, which is a macrocyclic depsipeptide with two backbone thiazole units and a dimethylated N-terminus. The two thiazole building blocks were synthesized from commercially available materials in four or fewer steps and employed directly in solid-phase peptide synthesis (SPPS) to afford pagoamide A. The use of SPPS ensured that the synthetic sequence is operationally straightforward and, if needed, permits modular substitution of building blocks to easily access diverse structural analogs. Our antimicrobial assays showed that pagoamide A has moderate activity against Bacillus subtilis.